2017
DOI: 10.22190/fueo1702093p
|View full text |Cite
|
Sign up to set email alerts
|

Market Size as a Determinant of the Foreign Direct Investment Inflows in the Western Balkans Countries

Abstract: Abstract. Numerous empirical studies confirm that market size is one of the key determinants of foreign direct investment inflows, particularly market-oriented projects of foreign direct investment. Basically, the dominant view is that a larger market of the host country attracts a greater quantum of foreign direct investment. This paper examines the influence of market size, as well as the impact of market growth, trade openness, and population size on the foreign direct investment inflows into the six countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…Results indicate that a percentage change in market size increases inflows of FDI by 2.32%. These results agree with the existing literature (see, for example, Jaiblai & Shenai, 2019;Faroh & Shen, 2015;Mottaleb & Kalirajan, 2010;Petrović-Ranđelović et al, 2017) in the case of Sub-Saharan African region, Sierra Leone, in and low-income countries and Balkan countries). Thus, infrastructure quality, market size, and trade openness determines FDI attraction in the two regions.…”
Section: Presentation and Interpretation Of Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Results indicate that a percentage change in market size increases inflows of FDI by 2.32%. These results agree with the existing literature (see, for example, Jaiblai & Shenai, 2019;Faroh & Shen, 2015;Mottaleb & Kalirajan, 2010;Petrović-Ranđelović et al, 2017) in the case of Sub-Saharan African region, Sierra Leone, in and low-income countries and Balkan countries). Thus, infrastructure quality, market size, and trade openness determines FDI attraction in the two regions.…”
Section: Presentation and Interpretation Of Resultssupporting
confidence: 92%
“…Besides, GDP per capita measures the purchasing power of an economy in an internationally comparable way. Previous studies have found the variable to be positively related to the attraction of FDI inflows (see Petrović-Ranđelović et al, 2017).…”
Section: Description Of the Variables In The Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…After we run (ADM) method and Saaty procedure we got The experts saw that MS is the most important that they preferred it strongly more than the rest of our variables and this is consistent with many studies as (Petrović-Ranđelović et al, 2017) . (Belderbos et al, 2002;Blomström & Lipsey, 1991;Sun et al, 2002) that what we mentioned in market size section above.…”
Section: W=[ 2 ′′supporting
confidence: 80%